PENGARUH KOMITMEN ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA ANGGOTA BADAN KESWADAYAAN MASYARAKAT (BKM) PADA PROGRAM PNPM KOTA MATARAM - Rosmiati Rosmiati; hermanto hermanto; Thatok Asmony (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research was conducted in the community self-reliance organization. This research is aimed at determining the effect of organizational commitment and work motivation of members of Community self-reliance organization of urban national program of community empowerment in Mataram. The population of this research are 556 from which 85 respondents were selected. The data were analyzed using multiple linear regression. The research showed that organizational commitment and work motivation subsequently affect positively and significantly the performance of members of Community self-reliance organization of urban national program of community empowerment in Mataram.Keywords: organizational commitment, work motivation, performance